2006
DOI: 10.1016/j.mod.2006.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Gata3 is required for early morphogenesis and Fgf10 expression during otic development

Abstract: Inner ear develops from an induced surface ectoderm placode that invaginates and closes to form the otic vesicle, which then undergoes a complex morphogenetic process to form the membranous labyrinth. Inner ear morphogenesis is severely affected in Gata3 deficient mouse embryos, but the onset and basis of the phenotype has not been known. We show here that Gata3 deficiency leads to severe and unique abnormalities during otic placode invagination. The invagination problems are accompanied often by the formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
87
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(103 citation statements)
references
References 49 publications
14
87
2
Order By: Relevance
“…Previously, Wnt signaling was shown to mediate otic versus epidermal fate decisions during the formation of otic placode (Lillevali et al 2006;Ohyama et al 2006). In the developing chicken inner ear, Fekete (2008, 2009) Lgr5 is an orphan G protein-coupled receptor with a large leucine-rich domain, but lacks a clearly defined function (Hsu et al 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, Wnt signaling was shown to mediate otic versus epidermal fate decisions during the formation of otic placode (Lillevali et al 2006;Ohyama et al 2006). In the developing chicken inner ear, Fekete (2008, 2009) Lgr5 is an orphan G protein-coupled receptor with a large leucine-rich domain, but lacks a clearly defined function (Hsu et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple genes are expressed within the cochlear prosensory domain, including Jagged1, Islet1, Lunatic fringe, Prox1, Sox2, and Fgf20 (Bermingham-McDonogh et al 2006;Dabdoub et al 2008;Hayashi et al 2008;Kiernan et al 2005;Morrison et al 1999;Morsli et al 1998;Radde-Gallwitz et al 2004). Wnt/ß-catenin signaling is involved in the specification of otic cell identity, dorsal patterning of the otocyst, as well as eventual formation of the vestibular organs (Hollyday et al 1995;Jasoni et al 1999;Lillevali et al 2006;Ohyama et al 2006;Riccomagno et al 2005). However, few studies have examined the role of this signaling pathway in the developing cochlea in the late embryonic age.…”
Section: Introductionmentioning
confidence: 99%
“…6H,L and data not shown). Similarly, no change was observed in the expression of Gata3 at E12.5 or E14.5 (data not shown), which is at these stages expressed in restricted areas of vestibular nonsensory epithelium and periotic mesenchyme in addition to the sensory areas (Lillevä li et al, 2004(Lillevä li et al, , 2006. In summary, these observations suggested that the inactivation of Gata2 did not cause any major defects in cell differentiation and fate determination of the otic epithelium.…”
Section: Developmental Dynamicsmentioning
confidence: 59%
“…Gata2 is expressed in the developing inner ear of mouse and chicken together with another family member, Gata3 (Lillevä li et al, 2004(Lillevä li et al, , 2006. The expression of Gata2 starts in mouse otic vesicle at E9.5, while Gata3 expression is activated already in the otic placode (Lillevä li et al, 2004(Lillevä li et al, , 2006.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation